2022
DOI: 10.1177/2473974x211073306
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Fungating Wounds of the Head and Neck: Management and Antibiotic Stewardship

Abstract: Objective Malignant fungating wounds (MFWs) are unfortunate and underreported manifestations of some advanced head and neck cancers. The management of MFWs is complex and challenging. MFWs are often mistaken for infectious processes/abscesses and treated indiscriminately with oral or intravenous antibiotics. Our aim is to promote awareness of MFWs and provide education on their management. We summarize their cost-effective and evidence-based therapies and highlight antibiotic stewardship with respect to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…50 Considered collectively, findings from these studies indicate that malodor may be alleviated by several topical or systemic therapies including metronidazole, ionic silver, polyhexamethylene biguanide, green tea, manuka honey, nanocrystalline silver nanoparticles, and charcoal. 51 However, we found no significant differences between these interventions and no standard or consensus concerning the best dosage and route of these therapies. 13,19,20,52 We found several articles that evaluated systemic or topical agents for relief of pain in patients with MFW.…”
Section: Symptom Managementmentioning
confidence: 65%
See 1 more Smart Citation
“…50 Considered collectively, findings from these studies indicate that malodor may be alleviated by several topical or systemic therapies including metronidazole, ionic silver, polyhexamethylene biguanide, green tea, manuka honey, nanocrystalline silver nanoparticles, and charcoal. 51 However, we found no significant differences between these interventions and no standard or consensus concerning the best dosage and route of these therapies. 13,19,20,52 We found several articles that evaluated systemic or topical agents for relief of pain in patients with MFW.…”
Section: Symptom Managementmentioning
confidence: 65%
“…However, the small sample size in the study rendered it difficult to reflect the genuine effectiveness of systematic antibiotics in relieving symptoms of MFWs 9. A recent literature review suggested that prophylactic systemic antibiotics should be avoided for treating patients with MFWs 51…”
Section: Resultsmentioning
confidence: 99%
“…The use of systemic antibiotics should be limited to managing acute infection 44 . Bacterial colonisation of necrotic tissue leads to chronic infection which is best managed with an appropriate dressing regimen.…”
Section: Wound Assessmentmentioning
confidence: 99%
“…Over time, these wounds evolve and deteriorate, becoming more extensive and invasive (Hoshi et al, 2019; Tilley et al, 2020; Young, 2017). Approximately 4%–15% of cancer patients develop this type of injury (Firmino et al, 2020) that predominately involve breasts (62% to 66%), head and neck (24%), and the chest due to the proximity of the compromised tissue to the skin (EONS, 2015; Firmino et al, 2020; Neves Duarte Lisboa, 2016; O’Neill et al, 2022). According to the Haisfield‐Wolfe and Baxendale‐Cox staging system, people with MFWs in their advanced stages are beleaguered by debilitating symptoms, including odour, exudate, itching, bleeding and pain (Haisfield‐Wolde & Baxendale‐Cox, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, these wounds evolve and deteriorate, becoming more extensive and invasive (Hoshi et al, 2019;Tilley et al, 2020;Young, 2017). Approximately 4%-15% of cancer patients develop this type of injury (Firmino et al, 2020) that predominately involve breasts (62% to 66%), head and neck (24%), and the chest due to the proximity of the compromised tissue to the skin (EONS, 2015;Firmino et al, 2020;Neves Duarte Lisboa, 2016;O'Neill et al, 2022).…”
Section: Introductionmentioning
confidence: 99%